2009
DOI: 10.2340/16501977-0445
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 12-week Tai Chi Chuan exercise on peripheral nerve modulation in patients with type 2 diabetes mellitus

Abstract: Results from this study suggest that fasting blood glucose and peripheral nerve conduction velocities in diabetic patients can be improved by 12 weeks tai chi chuan exercise. A further larger randomized controlled clinical trial with longer follow-up time is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 20 publications
0
59
0
2
Order By: Relevance
“…DPN is frequently associated with pain, infection, and sensory loss in affected patients, leading to a variety of complications including falls. 20 The present study found significant improvements in the TSS for neuropathy and balance at the completion of the 12-week TCD program. In previous studies, diabetic patients who practiced TC exercise for more than 12 weeks reported higher cutaneous vascular conductance 14 as well as better peripheral nerve conduction velocities of the bilateral median and tibial nerves.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…DPN is frequently associated with pain, infection, and sensory loss in affected patients, leading to a variety of complications including falls. 20 The present study found significant improvements in the TSS for neuropathy and balance at the completion of the 12-week TCD program. In previous studies, diabetic patients who practiced TC exercise for more than 12 weeks reported higher cutaneous vascular conductance 14 as well as better peripheral nerve conduction velocities of the bilateral median and tibial nerves.…”
Section: Discussionmentioning
confidence: 58%
“…17 Previous studies looking at the effects of TC exercise on glucose control in diabetic patients have produced conflicting results. The findings of several studies support the beneficial effects of TC exercise on glucose control, 20,23 but a randomized study with the TCD program found no significant improvement on either glucose homeostasis or insulin sensitivity. 22 Tsang et al 22 found a small and nonsignificant effect size ( -0.07 -0.4%) on HbA1c levels after a 16-week TCD program.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…It develops early in the disease and tends to get worse over time with a prevalence ranging from 5 to 80%. It is associated with pain, infection and loss of sensitivity in affected patients 2,3 .…”
Section: Introductionmentioning
confidence: 99%